Application of buckling restrained braces to upgrade vertical stiffness of existing RC frames - Niyonyungu, Ferdinand; Noroozinejad, Farsangi Ehsan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this paper, based on the RC frame structure of an industrial building, the finite element model of the structure is developed, according to the Chinese code for seismic design of buildings [9]. Considering the lack of seismic performance, the buckling restrained brace (BRB) is adopted for seismic retrofitting, and various configurations of buckling restrained support are considered for reinforcement.
Keywords: frame structure; retrofitting; vertical stiffeners; restrained braces; nonlinear analysis; ramy żelbetowe; modernizacja; usztywnienie pionowe; klamry; analiza nieliniowa